A method of identifying mining disturbance in arid or semi-arid steppe using inter-annual Landsat images-a case study in north-eastern China. Issue 12 (2nd December 2018) - Yang, Zhen; Li, Jing; Yin, Shouqiang; Shen, Yingying
ABSTRACT: Mining disturbances affect the environmental quality, local ecology and human populations. Thus, a lot of public attention has been paid on mining issues and the need for the detection of mining disturbance. Research on mining disturbance identification is mainly for forested regions where other disturbances account for a very small areal proportion. It is more challenging to identify mining disturbance of arid or semi-arid steppe due to its vulnerable ecology and existence of other disturbances. In this letter, we proposed a method to identify mining disturbance for arid or semi-arid steppe using inter-annual Landsat images. The method utilizes both spectral characteristics and topology information. We applied the method to Bal Rishi Le mining area located in north-eastern China. By accuracy assessment, the method was proven to be reliable with 92.2% overall accuracy.